Uncovering the Mechanisms of Long-Range Magnetic Order in [Mn(mal)(H2O)]n: Insights from Microscopic and Macroscopic Magnetic Analysis - Fernando S. Delgado; Laura Cañadillas-Delgado; Juan Rodríguez-Carvajal; Óscar Fabelo; Jorge Pasán (Magnetochemistry)
In this study, we investigate the magnetic properties of the molecular compound [Mn(mal)(H2O)]ₙ (mal = dianion of malonic acid) by integrating microscopic and macroscopic characterization, combining unpolarized neutron diffraction and magnetometry measurements. Neutron diffraction, though non-commonly applied to molecular compounds, proved essential for fully resolving the magnetic structure, as well as overcoming challenges such as hydrogen-related incoherent scattering and difficulties in accurately locating light atoms. Our neutron data provided critical structural details, including the precise location of hydrogen atoms, especially those associated with crystallization water molecules. By conducting low-temperature measurements below the magnetic ordering temperature, we identified the correct Shubnikov space group (Pc’a21’) and established a magnetic model consistent with the observed weak ferromagnetism. Our findings reveal that the compound presents a spin-canted structure with a weak ferromagnetic signal along the b-axis. This signal originates primarily from antisymmetric exchange interactions rather than single-ion anisotropy, consistent with the isotropic nature of the Mn(II) (6A1g) ground state. The combined neutron diffraction and magnetometry results provide a comprehensive understanding of how structural and symmetry factors influence the magnetic properties of malonate-based manganese compounds.